Oculomotor capture is influenced by expected reward value but (maybe) not predictiveness. Issue 2 (February 2019) - Le Pelley, Mike E; Pearson, Daniel; Porter, Alexis; Yee, Hannah; Luque, David
A large body of research has shown that learning about relationships between neutral stimuli and events of significance – rewards or punishments – influences the extent to which people attend to those stimuli in the future. However, different accounts of this influence differ in terms of the critical variable that is proposed to determine learned changes in attention. We describe two experiments using eye-tracking with a rewarded visual search procedure to investigate whether attentional capture is influenced by the predictiveness of stimuli (i.e., the extent to which they provide information about upcoming events) or by their absolute associative value (i.e., the expected incentive value of the outcome that a stimulus predicts). Results demonstrated a clear influence of associative value on the likelihood that stimuli will capture eye-movements, but the evidence for a distinct influence of predictiveness was less compelling. The results of these experiments can be reconciled within a simple account under which attentional prioritization is a monotonic function of the expected, subjective value of the reward that is signalled by a stimulus.